2014
DOI: 10.1002/jmrs.79
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement process to assess tattoo alignment, set‐up accuracy and isocentre reproducibility in pelvic radiotherapy patients

Abstract: IntroductionThis quality improvement study tested three methods of tattoo alignment and isocentre definition to investigate if aligning lateral tattoos to minimise pitch, roll and yaw decreased set-up error, and if defining the isocentre using the lateral tattoos for cranio-caudal (CC) position improved isocentre reproducibility. The study population was patients receiving curative external beam radiotherapy (EBRT) for prostate cancer. The results are applicable to all supine pelvic EBRT patients.MethodsThe th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… 24 , 25 Thus, positioning patients with plump breasts using skin tattoos is challenging. 24 The degree of filling of the abdominal bladder directly affects the location of skin 26 tattoos, tumors, and internal organs. 27 Jhingran 28 et al.…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 25 Thus, positioning patients with plump breasts using skin tattoos is challenging. 24 The degree of filling of the abdominal bladder directly affects the location of skin 26 tattoos, tumors, and internal organs. 27 Jhingran 28 et al.…”
Section: Discussionmentioning
confidence: 99%
“…Although, with the growth of the modern state‐of‐the‐art image guidance systems for use in Image Guided Radiation Therapy (IGRT), including surface imaging systems, the dependence on and relevance of these marks has been drastically reduced 8, 9. With current standards of care, where volumetric imaging is employed prior to treatment for 3D setup corrections, subcutaneous marks serve as a relic of the pre‐volumetric imaging standards or positioning.…”
Section: Discussionmentioning
confidence: 99%
“…The use of additional lateral skin marks, with a single anterior mark, is recommended to minimise rotation. 10,11 While rotational errors could not be assessed in this analysis, Elsner et al 12 demonstrated lateral skin marks minimise rotation (roll and yaw) when used in conjunction with the anterior skin mark in pelvic patients. Similar to our study, systematic and random errors in the S-I directions were also reduced, and isocentre reproducibility improved.…”
Section: Discussionmentioning
confidence: 93%